Clinical impact of bone and connective tissue markers - Lindh, E. (Erik); Thorell, Jan I., 1934- (Pharmacia Diagnostics clinical symposia, 1989)
For many years, biochemical tests have been widely used for the diagnosis, classification, and monitoring of bone and connective tissue disease. However, shortcomings in terms of the specificity and sensitivity of such tests have prompted continual questioning about their clinical usefulness. This book, based on a meeting organized jointly by the University of Uppsala and Pharmacia Diagnostics AB, reviews our current understanding of basic bone and connective tissue biochemistry and the clinical role of biochemical markers specific to related diseases, with special reference to rheumatoid arthritis and osteoporosis.